The Importance of Language Contacts in the Field of Tourism - Kamala Avadır Jafarova (Indonesian Journal of Cultural and Community Development, 2020)
Tourism is not only a way of spending citizens' leisure time, it has transformed into a mass communication practice, a significant social process. Cross-cultural tourism is the most widespread, its purpose is to get acquainted with a different natural, ethno-social and cultural reality. International experience in the field of effective use of the tourism potential of the regions is based on language relations. Our goal is to reveal the exceptional role of language contacts in the further development of tourism. When we talk about tourism, we always remember the country's economy. But we must not forget that along with the economy, the development of language contacts play an important role in tourism. The question is as follow: Is there a need for specialists and consultants on cross-cultural relations in the field of tourism? This need is certainly overdue. The tourism industry today is not just a haphazard sector. It is a complex conglomerate of relationships between different types of structures. These are tour operators that create a product for the end user, intermediary agents, travel agencies, air carriers, hotels and resorts, rental offices (from cars to country villas and apartments), security systems, etc. For successful interaction of all these structures and development of the industry as a whole, professionals in cross-cultural relations are necessary. The problem becomes more relevant when the interaction of cultures goes beyond one country or region.